Role of entrepreneurial passion and entrepreneurial self- efficacy in developing students’ intention to become an entrepreneur: An evidence from Malaysia - Ahmad, Muhammad Azeem; Hashmi, Arshia; Arshad, Imran; ChikImLoh, (The journal of contemporary issues in business and government, 2021)
Using social cognitive theory as underpinning theoretical framework, the study aims to examine the role of entrepreneurial passion in influencing entrepreneurial self-efficacy among students that further leads to their intention to become an entrepreneur. Data was collected from the business and economics students of three universities located across Malaysia through a cross- sectional design. The results revealed one’s entrepreneurial passion positively effects students’ intention to launch a new venture after graduation. Whereas entrepreneurial self-efficacy offers an intervening mechanism that links and translates the impact of entrepreneurial passion on students’ entrepreneurial intention, the relationship that is also moderated by entrepreneurial education. The study thus addresses the call by past researchers on the missing link that unfold into to one’s entrepreneurial intention. Findings thereby provides the possible future directions of how person and context factors could leverage individuals’ entrepreneurial self-efficacy to facilitate the process to become an entrepreneur.